P023 Prevalence of malnutrition, risk of malnutrition and quality of life among patients with Inflammatory Bowel Disease. (21st January 2022) - Korwel, K M; Hjortswang, H; Eberhardson, M; Pihl Lesnovska, K
Abstract: Background: The relapsing and remitting course of inflammatory bowel disease (IBD) with inflammation and gut symptoms may result in an elevated risk of malnutrition and impaired quality of life. Patients with pro-longed active IBD are at the highest risk of developing impaired nutritional status. The aim of this study was to determine the prevalence of malnutrition and risk of malnutrition in outpatients with inflammatory bowel disease. Furthermore, to study their body composition, identify factors associated with malnutrition and investigate the association between malnutrition and quality of life. Methods: A total of 328 IBD outpatients, (154 [47 %] with Crohn's disease (CD) and 174 [53%] with ulcerative colitis (UC)) at Linköping University hospital were included in this population-based cross-sectional study. Patients underwent malnutrition assessment using the recently published Global Leadership Initiative on Malnutrition (GLIM) criteria. Data about body mass index, weight loss and dietary problems were collected and used to evaluate risk of malnutrition. The Short Health Scale (SHS) was used to measure quality of life. Results: Malnutrition was detected in 33 patients (10, 1 %) and 162 patients (55, 0 %) had an increased risk of malnutrition. Malnutrition was associated with lower quality of life in the entire patient cohort and there was no difference between diagnoses. The prevalence of malnutrition was significantly higher among women (73% vs 27 %). Malnourished patients and those at risk of impaired nutritional status were more likely to have had active disease during the preceding 12 months compared to patients without malnutrition or at risk of malnutrition (27 % vs 12% [p=0.015] and 15 % vs 7% [p=0.037] respectively). Surprisingly, a higher calprotectin value was detected among patients without risk of malnutrition when compared to those who were at risk (median 46 [IQR 17 – 106] vs 59 [IQR 25 – 288] respectively, p=0, 009). Women with IBD had significantly lower fat-free mass index (FFMI) compared to men. Patients with CD had reduced quality of life compared to patients with UC. Conclusion: The prevalence of malnutrition in IBD-outpatients was 10% and more than half of the participants were at risk of malnutrition. Malnutrition was associated with poor quality of life. Malnutrition screening might be important in this population as ongoing inflammation and active disease seem to be apparent even among patients without clear nutrition difficulties or weight problems, but might influence nutritional status and quality of life negatively in the long term. Patients with IBD should therefore be screened for malnutrition and risk of malnutrition on a regular basis.